2001
DOI: 10.1080/gye.15.4.279.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyproheptadine clorhydrate ,a serotonin receptor antagonist ,on endocrine parameters in weight-loss related amenorrhea

Abstract: The aim of the study was to evaluate the possible interactions and/or modulations of the serotoninergic system on hormonal parameters and the reproductive axis in amenorrheic subjects. Hypogonadotropic, underweight, amenorrheic patients (n = 8) were studied before and during cyproheptadine clorhydrate administration (4 mg/day for 3 months). A pulsatility study (4 hours, sampling every 10 minutes) and a naloxone test were performed before and after 4 and 12 weeks of treatment. Plasma luteinizing hormone (LH), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition, previous studies have shown that serum IGF-I is a sensitive index of nutritional repletion in malnourished children 23 increment of growth rate in the cyproheptadine group accompanied an increase in serum IGF-I concentration. By contrast, an increased 4-hour integrated mean GH concentration during 3 months cyproheptadine therapy in underweight amenorrheic patients was demonstrated 25 . Given the evidence of blunting of the GH response during GH provocative testing in cyproheptadinetreated individuals 13 " 15 , cyproheptadine therapy may therefore have a detrimental effect, if any, on 24hour integrated GH secretion, and consequently may attenuate IGF-I secretion.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, previous studies have shown that serum IGF-I is a sensitive index of nutritional repletion in malnourished children 23 increment of growth rate in the cyproheptadine group accompanied an increase in serum IGF-I concentration. By contrast, an increased 4-hour integrated mean GH concentration during 3 months cyproheptadine therapy in underweight amenorrheic patients was demonstrated 25 . Given the evidence of blunting of the GH response during GH provocative testing in cyproheptadinetreated individuals 13 " 15 , cyproheptadine therapy may therefore have a detrimental effect, if any, on 24hour integrated GH secretion, and consequently may attenuate IGF-I secretion.…”
Section: Discussionmentioning
confidence: 80%
“…All these situations lead to or amplify the disruption of the hypothalamus-pituitary activity controlling ovarian function (1,7,(23)(24)(25). In the last decade, various therapeutic strategies have been proposed to recover the reproductive function of patients affected by FHA who are trying to avoid the use of oral contraceptives, such as naltrexone chlorohydrate, an opioid receptor antagonist (26)(27)(28), cyproheptadine, a serotonin receptor antagonist, (29) or acetyl-L-carnitine (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cyproheptadine also appeared to stimulate appetite and decrease diarrhea in patients with advanced carcinoid tumors [113]. Studies on the effects of cyproheptadine in progressive weight loss in patients with cancer or other causes of cachexia suggest that cyproheptadine has a beneficial effect on appetite stimulation but only slight effects on weight gain [110, 114, 115]. 5-hytroxytryptamine type 3 (5HT3) receptor antagonists, such as ondansetron and granisetron, have entered widespread clinical use as antiemetics for cancer chemotherapy [99].…”
Section: Managing Cancer Cachexiamentioning
confidence: 99%